1973
DOI: 10.1037/h0035278
|View full text |Cite
|
Sign up to set email alerts
|

Reexamination of role of familiarization in retrograde amnesia in the rat.

Abstract: Rats were given a single familiarization (FAM) session before training in a one-trial passive-avoidance task and were then submitted to hypoxia or eleotrooonvulsive shock (ECS) in an attempt to produce retrograde amnesia (RA). Another group received the same training and posttraining treatment but not prior FAM. The results indicate that under the present training conditions, prior FAM is a necessary condition for both hypoxia and ECS to produce RA. These results are considered to underline the need to modify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

1974
1974
1991
1991

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…Furthermore, this adaptive behavior cannot be attributed to new information about response contingencies since no step-through response is made and the animal is exposed to neither shock chamber before the expression of avoidance behavior. The results support the point of view that memory traces survive ECS but in a primitive form, which must be integrated into existing functional systems (see Sara & Lefevre, 1973). This memory elaboration (Lewis, 1969) or integration probably takes place at least partially after learning, and the amnestic treatment prevents this activity.…”
Section: Discussionsupporting
confidence: 82%
“…Furthermore, this adaptive behavior cannot be attributed to new information about response contingencies since no step-through response is made and the animal is exposed to neither shock chamber before the expression of avoidance behavior. The results support the point of view that memory traces survive ECS but in a primitive form, which must be integrated into existing functional systems (see Sara & Lefevre, 1973). This memory elaboration (Lewis, 1969) or integration probably takes place at least partially after learning, and the amnestic treatment prevents this activity.…”
Section: Discussionsupporting
confidence: 82%
“…Quartermain et al, 1972;Sara, 1973 a, b) has led to the proposal that the effect of these agents is not on storage processes but on retrieval mechanisms (see Spear, 1973). Memory consolidation or storage is probably completed in a very short period of time (Chorover and Schiller, 1965), but the memory is not available to effect behavior unless it is integrated into existing functional systems (see Sara and Lefevre, 1973). It is this integrative activity which is interrupted or prevented by the amnestic agent.…”
Section: Introductionmentioning
confidence: 96%
“…Misanin (1968, 1969) found that animals were less likely to suffer retrograde amnesia from ECS treatment when they were familiar with the situation. However, this has not been confirmed by other research (Sara & Lefevre, 1973 Request for reprints should be sent to Toshitsugu Hirano, Department of Psychology, Kyoto University, Kyoto, 606 Japan. a view to examine the effect of familiarization upon retrograde amnesia produced by ECS or HAD, an experiment of conditioned emotional response (CER) was conducted and its extinction was tested by a method similar to that of Gustafson, Lidsky, and Schwartzbaum (1975…”
mentioning
confidence: 81%